let f, f9 be Function of REAL,REAL; :: thesis: ( ( for x being Real holds f . x = (a * x) + b ) & ( for x being Real holds f9 . x = (a * x) + b ) implies f = f9 )

assume that

A2: for x being Real holds f . x = (a * x) + b and

A3: for x being Real holds f9 . x = (a * x) + b ; :: thesis: f = f9

assume that

A2: for x being Real holds f . x = (a * x) + b and

A3: for x being Real holds f9 . x = (a * x) + b ; :: thesis: f = f9

now :: thesis: for x being Element of REAL holds f . x = f9 . x

hence
f = f9
by FUNCT_2:63; :: thesis: verumlet x be Element of REAL ; :: thesis: f . x = f9 . x

thus f . x = (a * x) + b by A2

.= f9 . x by A3 ; :: thesis: verum

end;thus f . x = (a * x) + b by A2

.= f9 . x by A3 ; :: thesis: verum